2019
DOI: 10.1007/s11842-019-09417-5
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Analysis of Residual Stand Damage Due to Winching on Steep Terrains

Abstract: Damage to the remaining stand on steep terrain can be quite severe and is usually difficult to control during winching. Timber skidding, especially by agricultural tractor, is a common solution in small-scale forestry. One of the factors influencing remaining stand damage is winching on steep terrain, although, to date, this has only been studied in general. Limiting stand damage is possible when the factors causing the damage are well-known. Therefore, the aim of this paper was to study in detail the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
3
30
1
Order By: Relevance
“…Both in summer and in winter a greater number of cases of damage were recorded in the phloem zone, with damaged bark and exposed phloem (80%), while the remainder were deep wounds reaching the xylem. A comparable percentage of bark removal (70%) in pine stands and a lower percentage in beech stands (30-40%) were reported by Picchio et al [46]. Those authors also recorded at least a 30% incidence of xylem damage in both types of stands.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both in summer and in winter a greater number of cases of damage were recorded in the phloem zone, with damaged bark and exposed phloem (80%), while the remainder were deep wounds reaching the xylem. A comparable percentage of bark removal (70%) in pine stands and a lower percentage in beech stands (30-40%) were reported by Picchio et al [46]. Those authors also recorded at least a 30% incidence of xylem damage in both types of stands.…”
Section: Discussionsupporting
confidence: 78%
“…Danilović et al [24] reported that in pure beech stands wounds with a surface area exceeding 200 cm 2 accounted for 52.6% of the total, while in mixed stands the figure was 43.4%. In turn, in a study by Picchio et al [46] wounds of 25-100 cm 2 predominated, and the share of larger wounds was also considerable.…”
Section: Discussionmentioning
confidence: 86%
“…Despite the challenging situation in the steep stand A, no effect on the rates of damaged remnant trees became obvious with respect to terrain slope or stand characteristics. Surprisingly, the steep stand A presented the lowest degrees of damaged basal area and volume compared to stands B and C. Differently, Picchio et al [32] described that damage to the remaining stand on steep terrain can be quite severe and is usually difficult to control. These authors also showed that the share of wounded trees was directly related to slope steepness, with larger wounds on steeper slopes.…”
Section: Discussionmentioning
confidence: 92%
“…A lower level of damage was observed after cable-skidding and ranged from 4.9 to 7.1% [18]. Stańczykiewicz et al [74] studied the damage of regeneration using two systems: (1) a tower cable system combined with farm tractor and (2) a skidder in a mature spruce stand. The damage of regeneration using the tower cable system (23.9%) was lower than using the skidder system (61.3%).…”
Section: How Muchmentioning
confidence: 99%
“…8. Alternatively, when possible and when financially acceptable, different forms of extraction should be used, for example, cable cranes or traction-winch-supported forwarders [74]. 9.…”
Section: Limiting and Preventing Damage To Regenerationmentioning
confidence: 99%